1994
DOI: 10.1111/j.1476-5381.1994.tb13152.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antinociception induced by supraspinally administered l‐arginine and kyotorphin

Abstract: Intracerebroventricular (i.c.v.) or intracisternal (i.cist.) administration of kyotorphin (KTP), an endogenous Met‐enkephalin releaser, at 5 μg per mouse, and l‐arginine (l‐Arg), a possible KTP precursor, at 30 μg per mouse, elicited antinociception in mice to a similar extent, as assessed by the tail‐flick test. Intracisternal preadministration of anti‐KTP serum abolished the effects of i.cist. KTP and i.c.v. or i.cist. l‐Arg, but not of i.c.v. KTP. The antinociceptive effects of i.cist. KTP and of i.c.v. or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The analgesia induced by kyotorphin lasts longer than that induced by Met-enkephalin. The analogue D-kyotorphin [L-Tyrosine-D-Arginine] (D-KTP) produces also analgesic effects by the introduction of Met-enkephalin release [1][2][3]. D-KTP is found to be more stable enzymatically in the brain therefore shows higher in vivo analgesic activity than does KTP [2,3].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The analgesia induced by kyotorphin lasts longer than that induced by Met-enkephalin. The analogue D-kyotorphin [L-Tyrosine-D-Arginine] (D-KTP) produces also analgesic effects by the introduction of Met-enkephalin release [1][2][3]. D-KTP is found to be more stable enzymatically in the brain therefore shows higher in vivo analgesic activity than does KTP [2,3].…”
Section: Introductionmentioning
confidence: 97%
“…It displays opioid type actions, including analgesic effects by releasing opioid pentapeptide Met-enkephalin from slices of the brain and spinal cord [1]. The analgesia induced by kyotorphin lasts longer than that induced by Met-enkephalin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that NO may have pronociceptive effects [1,2,11,12] or exert antinociception [3,13] at the spinal cord level. Others report that NO produces dual effects on nociception, depending on the dose and the pain model [6] .…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that intracerebroventricular (i.c.v.) injection of L-arginine (L-Arg) can elicit antinociception in mice [3] . Another study suggests that NO plays dual roles in nociception in the brain or in the periphery [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…NO is also part of the NMDA (N-Methyl-D-aspartic acid) receptor-coupled mechanism responsible for the activation of the c-fos gene (Garthwaite et al, 1988) and diffuses from neuronal cell bodies or dendritic/axonal processes to induce Fos expression in neighboring neurons (Salter et al, 1996). NOS inhibitors reduce Fos expression as well as nociceptive behavior following formalin injection in the hind paw (Chapman et al, 1995;Kawabata et al, 1994;Roche et al, 1996).…”
Section: Introductionmentioning
confidence: 99%